Considerations on how to investigate planes of satellite galaxies. Issue 7 (29th September 2017) - Pawlowski, Marcel S.; Dabringhausen, Jörg; Famaey, Benoit; Flores, Hector; Hammer, François; Hensler, Gerhard; Ibata, Rodrigo A.; Kroupa, Pavel; Lewis, Geraint F.; Libeskind, Noam I.; McGaugh, Stacy S.; Merritt, David; et al.
Abstract : The existence of a spatially thin, kinematically coherent Disk of Satellites (DoS) around the Milky Way (MW) is a problem that often garners vivacious debate in the literature or at scientific meetings. One of the most recent incarnations of this wrangle occurred with two papers by Maji et al., who argued that these structures "may be a misinterpretation of the data." These claims are in stark contrast to previous works. Motivated by this and other recent publications on this problem, we discuss necessary considerations to make, observational effects to consider, and pitfalls to avoid when investigating satellite galaxy planes such as the MW's DoS. In particular, we emphasize that conclusions need to have a statistical basis including a determination of the significance of satellite alignments, observational biases must not be ignored, and measurement errors (e.g., for proper motions) need to be considered. We discuss the general problems faced by attempts to determine the dynamical stability of the DoS via orbit integrations of MW satellite galaxies, and demonstrate that, to interpret simulations, it is helpful to compare them with a null case of isotropically distributed satellite positions and velocities. Based on these criteria, we find that the conclusions of Maji et al. do not hold up to scrutiny, and that their hydrodynamic cosmological simulation of a single host shows no evidence for a significant kinematic coherence among the simulated satellite galaxies, in contrast to the observed MW system.